A contextual policy analysis of a cash programme in a humanitarian setting: the case of the Emergency Social Safety Net in Turkey. Issue 3 (2nd December 2020) - Cetinoglu, Talita; Yilmaz, Volkan
Abstract : The Emergency Social Safety Net (ESSN) programme, which was launched in 2016, has become the central element of the humanitarian response to the plight of Syrian refugees in Turkey and an instrument of European migration control policies. This paper offers a contextual analysis of this European Union‐funded cash assistance scheme by examining the modes of interaction between its major assumptions and the broader humanitarian response in the context of Turkey. It finds that the ESSN comes with compromises on humanitarian principles and standards, amplifies the protection and assistance divide, and fails to address the realities of Turkey with respect to the country's housing and labour markets and weak protection framework. The paper concludes that a more inclusive approach to eligibility and higher transfer payments can contribute to the addressing of assistance needs provided that cash support is combined with robust protection programming and the implementation of sector‐specific projects and policies.